Semi Standardization of an Achievement Test in the Subject of Physics at Secondary Level - Bhatti, Sajjad Ahmad; Hashmi, Muhammad Aamir (Annals of Human and Social Sciences, 2025)
The objective of the study was to develop an achievement test of physics at secondary level. Item analysis is essential tool for reliability and validity of MCQs. For this a test comprising of 50 multiple-choice items was developed to measure lower order thinking skills of cognitive domain of Bloom’s Taxonomy. Convenience sampling technique was used to select a sample of 600 students. Mean and standard deviation for total sample were 37.10 ± 8.19, for male were 36.33 ± 8.91, for female were 37.84 ± 7.55, respectively. 17 items were easy, 31 items were moderate whereas 2 items were difficult. 48 items were good to discriminate among high and low achievers. All 50 items had effective distractors. Cronbach Alpha value was 0.92 and the face validity was 91.47%. The overall items should be made part of the test. Number of items be increased.